Acoustic analogue of electromagnetically induced transparency and Autler–Townes splitting in pillared metasurfaces. (18th October 2018) - Jin, Yabin; Pennec, Yan; Djafari-Rouhani, Bahram
Abstract: Electromagnetically induced transparency (EIT) and Autler–Townes splitting (ATS) originating from multilevel atomic systems have similar transparency windows in transmission spectra which causes confusion when discriminating between them, despite the difference in their physical mechanisms. Indeed, Fano interference is involved in EIT but not in ATS. There has been significant interest in the classic analogues of EIT and ATS in recent years, such as in photonics, plasmonics, optomechanics; however, the acoustic analogue of ATS has been rarely studied. In this work, we propose to investigate these phenomena in a pillared metasurface consisting of two lines of pillars on top of a thin plate. The existence of Fabry–Pérot resonance and the intrinsic resonances of the two lines of pillars act as a three-level atomic system that gives rise to the acoustic analogue of EIT and ATS. Since the frequency of Fabry–Pérot resonance can be tuned by controlling the distance between the two lines, the underlying physics, whether Fano interference is involved or not, is quite clear in order to discriminate between them. The realizations of EIT and ATS are put forward to control elastic waves for potential applications such as sensing, imaging, filtering.